Vascular involvement in systemic sclerosis (scleroderma) - Pattanaik D; Brown M; Postlethwaite AE (Dove Medical Press, 2011)
Debendra Pattanaik1, Monica Brown2, Arnold E Postlethwaite11Division of Connective Tissue Diseases, Department of Medicine; 2Section of Pediatric Rheumatology Department of Pediatrics, University of Tennessee Health Science Center, and Department of Veterans Affairs Medical Center, Memphis, TN, USAAbstract: Systemic sclerosis (SSc) is an acquired multiorgan connective tissue disease with variable mortality and morbidity dictated by clinical subset type. The etiology of the basic disease and pathogenesis of the systemic autoimmunity, fibrosis, and fibroproliferative vasculopathy are unknown and debated. In this review, the spectrum of vascular abnormalities and the options currently available to treat the vascular manifestations of SSc are discussed. Also discussed is how the hallmark pathologies (ie, how autoimmunity, vasculopathy, and fibrosis of the disease) might be effected and interconnected with modulatory input from lysophospholipids, sphingosine 1-phosphate, and lysophosphatidic acid.Keywords: fibrosis, autoimmunity, vasculopathy, S1P, LPA